The nursing team's compliance with hand hygiene: motivational factors - Annecy Tojeiro Giordani; Helena Megumi Sonobe; Gabriela Machado Ezaias; Maria Apparecida Valério; Denise de Andrade (Universidade Federal do Ceará, 2014)
This descriptive study aimed to verify factors which motivate compliance with hand hygiene on the part of the nursing team in a public hospital in Londrina, PR, Brazil, in 2012, and to propose strategies for improving this. A total of 135 nursing professionals participated, providing information on professional identification, continuing education, and the undertaking of hand hygiene. The motivation for complying with hand hygiene was linked to satisfaction in personal life for 45 (33.3%) and to satisfaction in the work for 58 (42.9%), as well as to autonomy for undertaking the nursing care, for 76 (56.3%). The motivational factors which influence compliance with the practice of hand hygiene were: professional development/growth, interest in the work, flexibility for prioritizing the care actions, autonomy, and participation in the decisions. These must be taken into account in planning the continuing education, so as to improve compliance with hand hygiene, as well as the quality of the care provided.